ANALISIS PRAKTIK TRANSFER PRICING PADA PT ADARO ANDALAN INDONESIA TBK DALAM PERUSAHAAN TERDAFTAR DI BEI (BURSA EFEK INDONESIA) - Johan Paulo Negos S; Jones Wahyu Simamora; Novita Yanti Sari Aritonang; Nesmada Putri Manullang; Putri Kemala Dewi Lubis (STKIP Subang, 2026)
This study aims to analyze the transfer pricing practices at PT Adaro Andalan Indonesia Tbk as a company listed on the Indonesia Stock Exchange (IDX). The study is motivated by the high volume of related-party transactions in multinational companies which may affect profit distribution and corporate tax obligations. The research employed a descriptive qualitative method with a case study approach. The data were obtained from the company’s 2025 interim financial statements, annual reports, and supporting data from the Indonesia Stock Exchange. Data collection was conducted through documentation studies by analyzing subsidiary structures, related-party transactions, and the company’s financial condition. The results indicate that the company has numerous subsidiaries located in Indonesia, Singapore, Mauritius, Malaysia, and Australia, which support transactions among entities within the same business group. In addition, related-party receivables amounting to USD 86,484 thousand and related-party payables amounting to USD 292,513 thousand were identified, indicating transfer pricing activities within the company’s operations. However, based on the financial statement analysis, these practices are still within applicable regulations and no direct evidence of tax violations was found. This study emphasizes the importance of implementing the arm’s length principle and maintaining transparency in related-party transactions to minimize the risk of transfer pricing abuse.